Numerical Investigation of Aluminum Extrusion of Feeder and Porthole Dies for Solid Profiles with Massive Wall Thickness Variation - Quang-Cherng Hsu (Springer, 2022)
Design of extrusion dies for complex solid profiles with varying wall thickness to ensure the flow balance in the extrudate is difficult. The type of dies and their structure, which directly affect the quality of the extruded product, are significantly influenced by experience of the designer. In this study, two types of dies, including feeder die and porthole die, were designed for extruding a complex heatsink profile. The basic dimensions of the feeder die were similar to the porthole die except for the bridge structure. Steady-state extrusion simulations of these two dies using HyperXtrude software were carried out. The numerical analysis results revealed that the porthole die with a unique bridge design offered a better distribution of velocity and residual stress in the extrudate than those of the feeder die. However, the port bridge structure of the hollow die caused a slight increase in temperature and extrusion force compared to the feeder die. Hence, the hollow die was considered as the optimal approach to achieve products with tight tolerance. To verify the numerical results, experiment extrusion of the heatsink profile using the hollow die was conducted on an industrial extruder. The results provide valuable information for engineers when designing extrusion dies of solid profiles with large variable wall thickness.